Oscar and Arabella and Ormsby - Layton, Neal. (London : Hodder Children's Books, 2008)
Best friends Oscar and Arabella learn the importance of making new friends when Ormsby joins the herd and wants to play.
Pub Weekly.
School Library Journal.
3.0
K-3
Keywords: Friendship -- Juvenile fiction; Mammoths -- Juvenile fiction; Friendship -- Fiction; Humorous stories; Mammoths -- Fiction; Friendship -- Fiction; Humorous fiction; Mammoths -- Fiction; Humorous fiction